1969
DOI: 10.1111/j.1476-5381.1969.tb08298.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of catecholamines and sympathetic stimulation on the release of acetylcholine from the guinea‐pig colon

Abstract: 1. In isolated guinea-pig terminal colon, the effect of sympathetic stimulation on contraction and acetylcholine release elicited by pelvic and transmural stimulation was investigated. 2. Sympathetic stimulation reduced the nerve-mediated contractile responses more than those produced by added acetylcholine. 3. Sympathetic stimulation also reduced the acetylcholine released during pelvic and transmural stimulation at low frequency. The inhibitory effect on acetylcholine released from resting colons is conceale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…Other workers have reported that continued stimulation does not maintain the cholinergic response (Garry & Gillespie, 1955;Rand & Ridehalgh, 1965;Bianchi, Beani, Frigo & Crema, 1968, Hukovic & Somogyi, 1969Kottegoda, 1969). Beani, Bianchi & Crema (1969) have shown that the rate of release of acetylcholine declines during extended stimulation of the intramural nerves of the guinea-pig colon at moderate frequencies. These results make it seem unlikely that secondary contractions are due to the persistence of the action of acetylcholine.…”
Section: Discussionmentioning
confidence: 98%
“…Other workers have reported that continued stimulation does not maintain the cholinergic response (Garry & Gillespie, 1955;Rand & Ridehalgh, 1965;Bianchi, Beani, Frigo & Crema, 1968, Hukovic & Somogyi, 1969Kottegoda, 1969). Beani, Bianchi & Crema (1969) have shown that the rate of release of acetylcholine declines during extended stimulation of the intramural nerves of the guinea-pig colon at moderate frequencies. These results make it seem unlikely that secondary contractions are due to the persistence of the action of acetylcholine.…”
Section: Discussionmentioning
confidence: 98%
“…Gershon (1967) did not find a reduction in acetylcholine output from the intestine when noradrenergic nerves were stimulated. Beani, Bianchi & Crema (1969) found that the mesenteric nerves reduced the output of acetylcholine only if parasympathetic nerves were stimulated at very low frequencies. suggested that splanchnic stimulation at <4 Hz acted via parasympathetic ganglia but at > 8.Hz it also appeared to have a direct effect on muscle.…”
Section: Introductionmentioning
confidence: 99%
“…When the preparation is given a train of stimuli there is an initial rapid fall in output per volley, followed by a relatively constant output (Paton, 1963 ;Paton & Vizi, 1969). Noradrenaline and adrenaline reduce the acetylcholine output per volley at low frequencies of stimulation (0-1-2 Hz) and this action is prevented by a-adrenoceptor blocking agents (Paton & Vizi, 1969;Kosterlitz, Lydon & Watt, 1970); sympathetic stimulation also inhibits acetylcholine release from guinea-pig colon (Beani, Bianchi & Crema, 1969) and from rabbit jejunum (Vizi, 1970).…”
Section: Introductionmentioning
confidence: 99%